The DFEL value methodology: a tool for design-for-environment in automotive industry - Mat Saman, Muhamad Zameri; Blount, Gordon (Faculty of Mechanical Engineering, 2008)

(untitled)
In the early 1990’s the European Union (EU) identified end-of-life vehicles as a priority waste stream and the EU Directive was introduced to protect the environment. Automotive companies are being pushed by environmental awareness and legislation to recycle, remanufacture and reuse components at the end of life and also to reduce the quantity of manufacturing waste generated. Within this scenario, a design tool is needed for vehicle design processes. Besides that, the role of design in modern manufacturing is becoming even more important with companies adopting design tools as profit generating business elements. Based on this requirement, the need was identified for a new methodology to analyse vehicles when they reach end-of-life situation especially in terms of design assessment and recyclability assessment. The aim of this paper is to give a description of the proposed tool for Design- for-End of Life Value (DFEL Value) in order to fulfil those requirements. There are two methodologies that facilitate the development of the DFEL Value concept; Recycling Function Deployment and Value Analysis. These two interrelated methodologies are primarily developed to assist automotive designers to design a vehicle for end-of-life purposes. This paper starts with the description of the methodology for Recycling Function Deployment analysis, followed by methodology for value analysis and lastly, the development of the prototype for DFEL Value. It takes into account the impact of the EU Directive and the solution to enhance the value of end-of-life vehicles. In the development process, several parameters in the product development process have been considered such as material types, joining techniques, product structure, environmental issues, economic consideration and also recycling technologies and facilities. Lastly, the paper presents an example of an automotive rear bumper as a case study in order to demonstrate and validate the proposed methodology.